2015
DOI: 10.1016/j.pharep.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of morphine–venlafaxine interactions in diabetic neuropathic pain model

Abstract: The results of our study show that single administration of VFX potentiates antinociceptive action of morphine in DNPM. This effect is probably mediated by both, noradrenergic and serotonergic systems. On the other hand, 21-days administration of VFX significantly decreases analgesic action of MRF. Moreover, there is a possibility that VFX acts as an antagonist of N-methyl-d-aspartate receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The authors speculate that venlafaxine might be a supplemental drug to restore the morphine analgesic effect. Similar findings had been published earlier in [269], where the authors showed that venlafaxine (10 mg/kg) increased the anti-pain effect of morphine (5 mg/kg) in rats with induced diabetic neuropathy. However, chronic prolonged administration of the antidepressant decreases this effect of morphine.…”
Section: Psychotropic Drugs For Management Of Pain and Itching Synsupporting
confidence: 91%
“…The authors speculate that venlafaxine might be a supplemental drug to restore the morphine analgesic effect. Similar findings had been published earlier in [269], where the authors showed that venlafaxine (10 mg/kg) increased the anti-pain effect of morphine (5 mg/kg) in rats with induced diabetic neuropathy. However, chronic prolonged administration of the antidepressant decreases this effect of morphine.…”
Section: Psychotropic Drugs For Management Of Pain and Itching Synsupporting
confidence: 91%
“…Accordingly, PCA administration was shown to reduce the anti-hyperalgesic effect (on mechanical hyperalgesia) of the repeated administration of venlafaxine (an SNRI) in STZ diabetic rats, suggesting a serotonergic mechanism in this effect [23]. The antidepressant also potentiated the antinociceptive action of morphine in the same context [24]. Pre-treatment clearly enhanced the analgesic activity of morphine, but the prolonged administration (21 days) of venlafaxine completely abolished the analgesic action of morphine in the STZ rat model [25].…”
Section: Effect Of Compounds Acting On Serotonergic Pathwaysmentioning
confidence: 96%
“…Another point, with regard to STZ-induced diabetes, is the different modalities of diabetes induction. For example, various routes of administration of STZ were used, either intramuscularly [23][24][25], intravenously [28,32,34,36,48] or intraperitoneally [27,29,33,35,39,40,45,49,56,[59][60][61][62]. These different methods do not allow us to compare data in an effective way, and even if some studies used identical routes of injection, the dose is different, ranging from 45 mg/kg [59] to 75 mg/kg [27].…”
Section: Comparison Of Animal Studies Exploring the Serotonergic Syst...mentioning
confidence: 99%